The neuromuscular fellowship portal and match. Issue 6 (9th March 2022) - London, Zachary N.; Gable, Karissa L.; Govindarajan, Ragav; Guidon, Amanda C.; Gwathmey, Kelly G.; Hehir, Michael K.; Imperioli, Matthew; Laughlin, Ruple S.; Price, Raymond S.; Sakamuri, Sarada; Sokol, Jacob; Baer, Michael
Abstract: For many years, Neuromuscular Medicine programs lacked a standardized means of handling fellowship applications and offering positions. Programs interviewed applicants and made offers as early as the first half of Post Graduate Year 3 (PGY3), a suboptimal timeline for applicants who may have had little prior exposure to neuromuscular or electrodiagnostic medicine. In 2021, the American Association of Neuromuscular & Electrodiagnostic Medicine (AANEM) developed the Neuromuscular Fellowship Portal to standardize a later timeline and establish a process for fellowship applications and offers. In its first year, the Neuromuscular Fellowship Portal used a unique one‐way match, in which the portal released serial offers to applicants based on rank order lists submitted by programs. Fifty‐two Neuromuscular Medicine programs and seven electromyography (EMG)‐focused Clinical Neurophysiology programs participated. Sixty‐eight positions were filled, a similar number to previous years. A survey of fellowship directors and applicants following this process showed overwhelming support for the standardized timeline and application portal, but all program directors and most applicants favored moving to a traditional match. To maintain the existing application timeline and minimize costs for all parties, the AANEM Neuromuscular Fellowship Portal will host a two‐way match, based on existing commercial match algorithms, in 2022. A match will afford a fair and efficient process for all involved. Both Neuromuscular Medicine and EMG‐focused Clinical Neurophysiology programs will be encouraged to participate. The process undertaken by the AANEM can stand as an example for other neurologic subspecialties who are interested in standardizing their application timeline.